Determination of tetracycline residues in pork meat from two slaughterhouses in Lima (2018) - Huanilo Tarazona, Jehason (2021)
The aim of this study was to determine the presence of tetracycline residues in pork in two herds of Lima during 2018. In total, 25 g of meat from the necks of 402 slaughtered pigs were processed. The samples were obtained in the cooling stage and evaluated using the microbiological diffusion technique, confronting the samples against the Bacillus subtilis strain ATCC 6633. Subsequently, the presence of tetracycline was confirmed by the ELISA MaxSignal Tetracycline Test Kit. None of the samples were positive to the microbiological diffusion test. However, 7.32% (6/82) were positive at a tetracycline concentration between 1587 and 5811 ppb. None of the positive samples exceeded the limits allowed in the country.